Application of the systematic cause analysis technique (SCAT) in preparing safety standard operating procedures at PT Hok Tong - Aswin, Budi; Manab, Abdul; Wardiah, Rizalia (Jurnal Kesmas Jambi, 2025)
Occupational accidents continue to occur in industrial environments, indicating gaps in workplace safety management and preventive controls. This study applies the Systematic Cause Analysis Technique (SCAT) to identify the root causes of work accidents and to develop safety standard operating procedures (SOPs) at PT Hok Tong.This research aims to analyze the application of the Systematic Cause Analysis Technique (SCAT) method in preparing work safety Standard Operating Procedures (SOP) at PT. Hok Tong Jambi, a natural rubber processing company that faces significant safety risks for its workers. Data was obtained through field observations, in-depth interviews with HSE staff and production workers, as well as reviewing work accident documents. Analysis using the SCAT model identifies the root causes of work accidents, including negligence, non-compliance with SOPs, and lack of adequate use of Personal Protective Equipment (PPE). This research found that factors such as lack of safety awareness, less than optimal supervision, and inconsistent implementation of SOPs were the main causes of work accidents in this company. Based on the results of the SCAT analysis, work safety SOPs were prepared as an effort to prevent and control work accidents, with the hope of increasing worker awareness and safe behavior. This research suggests strengthening supervision and more intensive safety training to minimize the risk of workplace accidents.